Determinants of tuberculosis incidence in East Asia and Pacific: A panel regression analysis - Mark Alipio (ZBW – Leibniz Information Centre for Economics, 2020)
Tuberculosis (TB) remains one of the world's deadliest communicable disease. To circumvent surges of TB cases, several studies have been carried out analyzing the determinants of TB incidence and recommended policy measures based on the significant indicators. Although the determinants were suggested for strategic planning of TB, the implementation of new measures was either unsuccessful or difficult to realize because of logistical, administrative, and financial constraints. This study aims to unravel potential determinants of TB incidence across 23 countries in East Asia and Pacific. The disentangling of possible association between variables was carried out using panel regression analysis. This is an ecological multinational-based study utilizing readily accessible public data in the analysis. Carbon dioxide emission, PM2.5 air pollution exposure, unemployment (percent of total labor force), percent of people using at least basic sanitation services, percent of people practicing open defecation, health expenditure (percent of GDP), and out-of-pocket health expenditure are included as the determinants of TB incidence. The single outcome variable of this study was TB incidence which is the estimated number of new and relapse tuberculosis cases arising in a given year, expressed as the rate per 100,000 population. A total of 23 countries in the East and Pacific region were included as sampling unit with a time-series length of five years (2010 – 2014), producing 115 samples. Given the nature of data, a panel regression was used to estimate the relationship between the potential determinants and TB incidence. A significant regression coefficient was found (F(7,107) = 37.9, p < 0.05) with R2 = 0.7126. The R2 value suggested that 71.26% of the variance in TB incidence was accounted for by the variables in this study. For every one unit increase in microgram per cubic meter of PM2.5 pollution, in the unemployment percentage of total labor force, and in the percentage of out-of-pocket health expenditure, the rate of TB cases per 100,000 population was predicted to be 4.617, 13.504, and 3.467 higher, respectively, holding other variables constant. On the other hand, for every one unit increase in the kiloton of CO2 emission and in the percent of people using at least basic sanitation services, the rate of TB cases per 100,000 population was predicted to be 0.00003828 and 4.457 lower, respectively. Percent of people practicing open defecation and health expenditure (percent of GDP) did not significantly influence TB incidence. The countries in the East Asia and Pacific with low PM2.5 air pollution exposure, low unemployment, low out-of-pocket health expenditure, high carbon dioxide emission and high percent of people using at least basic sanitation service, had low incidence of TB for the five-year period. The study suggests how an increase in unemployment consequently increases TB incidence across the countries. Proper implementation of programs that could promote proper hygiene is essential to increase adherence of people to basic sanitation practices. Based on the study, this is an important factor in mitigating higher incidence of TB. Therefore, strategies may be formulated to either maintain or improve this determinant in order to significantly reduce TB cases. Finally, concerted efforts may be developed to decrease emission of hazardous finer particles from residential, industrial, and agricultural burning, in order to control tuberculosis.
Keywords: A12; C4; C6; H51; I14; I15; I18; I38; 330; Carbon dioxide emission; air pollution; unemployment; sanitation; open defecation; health expenditure; out-of-pocket health expenditure; tuberculosis incidence; East Asia and Pacific; public health; economics